Allium ursinum as a Centuries-old Medicinal Plant. Short Review of Anti-inflammatory and Antimicrobial Properties of the Rare Garlic Species - Szczepaniak, Oskar; Neugart, Susanne; Przeor, Monika; Esatbeyoglu, Tuba (Planta Medica, 2025)
Wild garlic (Allium ursinum) is a wild plant growing in Middle and Eastern Europe that has been traditionally applied in local cuisine and herbal medicine practices. The leaves of the plant contain numerous bioactive compounds, i.e., flavonols, flavanols, phenolic acids, and thiopolysulfides. The aim of the study is to present the antioxidant, anti-inflammatory, and antimicrobial properties of this plant. The leaves of Allium ursinum possess strong antioxidant activity, which varies depending on extractant use and plant origin. The plant has limited capacity for ferric ion reduction in a FRAP test, as well. The previous studies showed that the high content of phenolic compounds was prevalently responsible for the high antiradical capacity. On the other hand, the thiopolysulfides present in the plant are responsible for its anti-inflammatory effect, observed as inhibition of TNF-α and interleukins, and as a bactericidal effect against skin pathogenic microflora. Wild garlic has a negative effect on cancer cell line viability, while it enhances the viability of non-cancerogenic tissue cells. All these effects clearly show that wild garlic is an interesting and potent raw material that should be more often applied in todayʼs functional foods, as well as a novel additive for dietary supplements, herbal remedies, or materials with topical anti-bacterial action.
Keywords: Allium ursinum; Allioideae; thiopolysulfides; antioxidant activity; anti-inflammatory effect; antibacterial effect